The impact of migration on adult mortality in rural South Africa: Do people migrate into rural areas to die? - Welaga, Paul (My University, 2007)
Objective This work investigates the hypothesis that individuals recently migrating into rural areas have a higher mortality than those always resident and that migrant deaths are more likely to be HIV/AIDS related than non migrant deaths. Methods Data from the Africa Centre Demographic Surveillance System (ACDIS), South Africa, was used for the analysis. A total of 41519 adults aged 18 to 60 years since their last visit dates were categorized into three groups; internal migrants, external in migrants and always resident individuals since 2001. Follow up period was from 1st January 2001 to 31st December 2005. Cox proportional hazard regression method was used to quantify the additional risk of dying for migrants who have recently migrated into the DSS area. Logistic regression was used to examine the relationship between migration status and dying from AIDS related complications for the members in the sample whose cause of death have been identified using verbal autopsy procedures. Results External in migrants into the DSS area were 1.52 times more likely to die than those always resident. After adjusting for the effects of sex, age group, socio-economic status and educational level an external in migrant has a relative risk of 1.19, [adjusted HR=1.19, P=0.001, 95% CI (1.08,1.32)] of dying compared to those always resident. Internal migrants were 18% less likely to die compared to always resident individuals, [adjusted HR=0.82, P=0.008, 95% CI (0.71, 0.95)] and males were 1.38 times more likely to die within the follow up period compared to females, [HR=1.38, P<0.001, 95% CI (1.28, 1.49)]. These results were statistically significant at 95% confidence level. Out of a total of 1119 deaths that occurred in 2001 and 2002 whose cause of death have been identified through verbal autopsy procedures, 763 (66%) died of AIDS. The odds of dying from AIDS are 2.09 if you are an external in migrant compared to an always resident member, [unadjusted OR = 2.09, P = 0.009 95% CI (1.38, 3.16)]. After controlling for other factors in the model, the odds of dying from AIDS as an external immigrant was 1.79 times, [adjusted OR = 1.79, P = 0.009, 95% CI (1.15, 2.77)] compared to those always resident. There was no significant difference in AIDS mortality between always resident individuals and internal migrants. The odds of a female dying of AIDS was 2.33 times, [OR = 2.33, P<0.001, 95% CI (1.78, 3.06)] compared to males after controlling for migration status, age, socioeconomic status and educational level. Conclusion External in migrants have an increased risk of death among adults aged 18 to 60 years compared to those always resident. External in migrants are also more at risk of dying from AIDS related illnesses than those always resident. Internal migrants are less likely to die than those always resident. Females are more at risk of dying from AIDS than males. In resource-poor settings, especially in many parts of Africa and other developing countries with very high prevalence of HIV/AIDS and over burdened health services in rural areas, it is important to identify and quantify some of these trends contributing to high disease burdens and mortality in rural areas in order to put in place effective interventions to better the health conditions of the people in these areas.
Student Number : 0516841M - MSc research report - School of Public Health - Faculty of Health Sciences
Keywords: adult mortality; migration status; AIDS mortality; verbal autopsy